2011
DOI: 10.2463/mrms.10.133
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Carcinoma of the Breast: MR Findings Correlated with Histopathology

Abstract: We correlateˆndings from magnetic resonance (MR) imaging and pathology in a 55-year-old woman with spindle cell carcinoma of the breast. Pathological examination showed aˆbrous capsule at the margins and abundantˆbromyxoid stroma within the mass. Spindle cell carcinoma may be included in the diŠerential diagnosis of expanding round masses with internal components that demonstrate rapid initial enhancement with high signal intensity on T 2 -weighted images in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Of 5 tumors available MRI-pathological correlation, 3 tumors showed hypointense rim on FST2WI, and all corresponded to a fibrous capsule (sensitivity, 75%; positive predictive value, 100%). It has been reported that 1 case of SpCC showed a heterogeneous, hyperintense, oval mass with an irregular hypointense rim on FST2WI, which corresponded with a fibrous capsule at the margin of the tumor on pathological findings 17 . As for the hypointense rim on FST2WI, Isomoto et al 17 supposed that it indicated an expanding growth pattern of the tumor.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Of 5 tumors available MRI-pathological correlation, 3 tumors showed hypointense rim on FST2WI, and all corresponded to a fibrous capsule (sensitivity, 75%; positive predictive value, 100%). It has been reported that 1 case of SpCC showed a heterogeneous, hyperintense, oval mass with an irregular hypointense rim on FST2WI, which corresponded with a fibrous capsule at the margin of the tumor on pathological findings 17 . As for the hypointense rim on FST2WI, Isomoto et al 17 supposed that it indicated an expanding growth pattern of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that 1 case of SpCC showed a heterogeneous, hyperintense, oval mass with an irregular hypointense rim on FST2WI, which corresponded with a fibrous capsule at the margin of the tumor on pathological findings. 17 As for the hypointense rim on FST2WI, Isomoto et al 17 supposed that it indicated an expanding growth pattern of the tumor. However, in our cases, it did not correlate with tumor size.…”
Section: Presence Absencementioning
confidence: 99%
See 2 more Smart Citations
“…Spindle cell metaplastic carcinoma (SpCMC) of the breast is a rare variant of breast cancer that has been classified under the category of metaplastic carcinoma (MC), a distinct entity within the group of undifferentiated invasive carcinomas, according to the World Health Organization (WHO) . Although this subtype was not continued into the following editions of WHO, it was still used in some newly published works . In the 4th edition of the WHO classification of breast tumors, it was definitely classified into the MC subtypes…”
Section: Introductionmentioning
confidence: 99%